Influencing factors on the preservation of lytic bacteriophage VP3 - Yue Xiao; Pin Huang; Zhenzhou Huang; Keyi Yu; Yang Song; Ning Guo; Hang Dai; Mengnan Jiang; Yi Xu; Duochun Wang; Qiang Wei (Elsevier, 2022)
Long-term and stable preservation of bacteriophages is of crucial importance. Although many efforts have been made in the past decades to explore the influence of external factors on bacteriophage preservation, there is still little understanding, and a systematic description is lacking. In this study, we explored the influence of different factors on the preservation of lytic bacteriophage VP3, one of the typing bacteriophages of Vibrio cholerae O1 biotype El Tor, and attempted to optimize its preservation. We examined external factors, including temperature, solution, and cryoprotectant, in stable cooling/freezing conditions or alternate cooling/freezing and thawing. We found that whether in Luria-Bertani (LB) medium or SM buffer, in terms of 20-week stable cooling or freezing, −20 °C was the most damaging while 4 °C, −80 °C, and −196 °C were protective. Thirteen cycles of alternate cooling/freezing and thawing caused a loss in the survival rates of bacteriophages. The addition of cryoprotectant, glycerol (30%, w/v) or dimethyl sulfoxide (DMSO, 10%, w/v) significantly improved the survival rates of bacteriophages preserved at −20 °C. However, at 4 °C, −80 °C, and −196 °C, the cryoprotectant effect was only slightly positive or even harmful. In summary, for bacteriophage VP3, the best preservation method is to directly preserve the bacteriophage stocks in LB medium at −80 °C or −196 °C instead of storing them in SM buffer or adding cryoprotectant. Our results provided insights into the external influencing factors on bacteriophage VP3 during preservation at low temperature and can be applied to the optimization of bacteriophage preservation in the future.